Commonwealth Caribbean legal literature : a bibliography of all primary sources to date and secondary sources for 1971-85 - Newton, Velma (UWI. Faculty of Law Library BridgetownBB, 1987)
Contains references to all known Commonwealth Caribbean legislation, law reports and post 1960 constitutions; a selection of treaties made between the Commonwealth and other countries; periodicals published in the region or those regularly containing articles pertaining to the region; bibliographies of legal and law related publications; articles and books in the field of law and law related areas; theses completed by students of the Faculty of Law, UWI, in partial fulfilment of the requirements for the LLB and higher degrees and theses completed outside the region on topics relating to Commonwealth Caribbean law.